2016
DOI: 10.1039/c5cp06179b
|View full text |Cite
|
Sign up to set email alerts
|

Voltage hysteresis of lithium ion batteries caused by mechanical stress

Abstract: The crucial role of mechanical stress in voltage hysteresis of lithium ion batteries in charge-discharge cycles is investigated theoretically and experimentally. A modified Butler-Volmer equation of electrochemical kinetics is proposed to account for the influence of mechanical stresses on electrochemical reactions in lithium ion battery electrodes. It is found that the compressive stress in the surface layer of active materials impedes lithium intercalation, and therefore, an extra electrical overpotential is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 169 publications
(119 citation statements)
references
References 39 publications
3
116
0
Order By: Relevance
“…Hence, in order to investigate the relationship between the electrochemically driven stress and disintegration of CuS, qualitative stress profile is obtained based on modified Butler-Volmer equation including a stress term (Figure 3a) [21,22] Hence, in order to investigate the relationship between the electrochemically driven stress and disintegration of CuS, qualitative stress profile is obtained based on modified Butler-Volmer equation including a stress term (Figure 3a) [21,22] …”
Section: Morphological Evolution Of Cus Nanoplates Upon Cyclingmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, in order to investigate the relationship between the electrochemically driven stress and disintegration of CuS, qualitative stress profile is obtained based on modified Butler-Volmer equation including a stress term (Figure 3a) [21,22] Hence, in order to investigate the relationship between the electrochemically driven stress and disintegration of CuS, qualitative stress profile is obtained based on modified Butler-Volmer equation including a stress term (Figure 3a) [21,22] …”
Section: Morphological Evolution Of Cus Nanoplates Upon Cyclingmentioning
confidence: 99%
“…Stress Profile Calculation: Stress-induced overpotential profile in Figure 3 is obtained using modified Butler-Volmer equation including a stress effect [21] …”
Section: Wwwadvancedsciencecommentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the overpotential, which is the difference between the real‐time and equilibrium potentials, is used to characterize the difficulty of reaction. The overpotential is negative when lithiated and positive when delithiated, and smaller overpotential absolute values signify smaller amounts of energy needed for lithiation and an easier lithiation reaction . Next, we further analyze how stress affects the overpotential and the reaction by means of mechanical models.…”
Section: Results Of Electrochemical Behavior Responses Under Active Smentioning
confidence: 99%
“…have analyzed the dependent relationship of potential with the state of the coupled stress . Song and co‐workers have found that coupled compressive stress impedes lithiation and therefore results in a higher overpotential using a modified Butler–Volmer equation . More related studies have indicated that lithium‐ion diffusion and lithiation‐induced crack in electrodes are significantly influenced by coupled stress during the electrochemical process .…”
Section: Introductionmentioning
confidence: 99%